2019
DOI: 10.3390/ijms20020374
|View full text |Cite
|
Sign up to set email alerts
|

Role of Semaphorins in Immunopathologies and Rheumatic Diseases

Abstract: Rheumatic diseases are disorders characterized by joint inflammation, in which other organs are also affected. There are more than two hundred rheumatic diseases, the most studied so far are rheumatoid arthritis, osteoarthritis, spondyloarthritis, systemic lupus erythematosus, and systemic sclerosis. The semaphorin family is a large group of proteins initially described as axon guidance molecules involved in nervous system development. Studies have demonstrated that semaphorins play a role in other processes s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 85 publications
1
23
0
Order By: Relevance
“…Next, we investigated the possible molecular mechanisms involved in the elevated severity of arthritis in this murine model. First, we analyzed expression of the Sema3B receptors, the plexin A family members, and the coreceptors neuropilin 1 (NRP-1) and NRP-2 (5)(6)(7)19). We found that expression of Nrp1 and Plexina2 was significantly lower in the joints of arthritic Sema3B −/− mice compared to the joints of WT and Sema3B −/− nonarthritic mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we investigated the possible molecular mechanisms involved in the elevated severity of arthritis in this murine model. First, we analyzed expression of the Sema3B receptors, the plexin A family members, and the coreceptors neuropilin 1 (NRP-1) and NRP-2 (5)(6)(7)19). We found that expression of Nrp1 and Plexina2 was significantly lower in the joints of arthritic Sema3B −/− mice compared to the joints of WT and Sema3B −/− nonarthritic mice.…”
Section: Resultsmentioning
confidence: 99%
“…Semaphorin 3B (Sema3B) is a secreted protein belonging to the semaphorin family involved in different biologic processes, such as apoptosis, angiogenesis, cell migration, and invasion (5)(6)(7). A recent study from our group implicated Sema3B in the pathogenesis of RA (8).…”
Section: Introductionmentioning
confidence: 99%
“…Sema3A becomes an immunosuppressive regulator that can initiate an immune inhibitory response by making a complex with neuropilin-1 and plexin-A4 [33]. This action was proven in several studies through the induction of Sema3A expression in animal models with arthritis and reported reduced severity and damage of articular surface [34].…”
Section: Discussionmentioning
confidence: 97%
“… 51 Semaphorin 3D, encoded by SEMA3D , is a member of the semaphorin family of axon guidance factors involved in nervous system development. 52 Evidently, semaphorins, such as SEMA3A , may be a potential target in OA, although the detailed roles of this family remain to be elucidated.…”
Section: Discussionmentioning
confidence: 99%